From the ground up: Impacts of a pro-poor community driven development project in Nigeria - Nkonya, Ephraim M.; Phillip, Dayo; Mogues, Tewodaj; Pender, John L.; Yahaya, Muhammed Kuta; Adebowale, Gbenga; Arokoyo, Tunji; Kato, Edward (International Food Policy Research Institute, 2008)
Poverty remains entrenched in Nigeria, where 70 percent of the rural population lives below the poverty line. In response, the Nigerian government launched the Second National Fadama Development Project (Fadama II) in 2005. Based on the community-driven development (CDD) approach, the project aims to generate income for beneficiaries, empower local communities, and improve the way governments reach poor and vulnerable groups, such as women, the elderly, disabled, and people with HIV/AIDS.--Authors' Abstract